EFECTO DE LA EMERGENCIA, CRECIMIENTO Y PRODUCCIÓN EN EL CULTIVO DE PIMIENTO AMARILLO (Capsicum annuum) CON LA BIOFERTILIZACIÓN DEL ALGA MARINA (Ascophyllum nodosum) - VEAS VÉLEZ, DAYRA KAROLINA (2023)
The objective of this research was to determine the emergence, growth and production of the yellow bell pepper crop by applying a biofertilizer based on Ascophyllum nodosum algae at different doses. A completely randomized design was used, with five treatments and four replications. The treatments correspond to T0 and different concentrations of A. nodosum algae T1-100%, T2-75%, T3-50% and T4-25%. Forty plants were used per treatment. The results indicated that the biofertilization with A. nodosum algae prior to sowing had a representative incidence on the plant, obtaining the highest number of germinated seeds in the vegetative parameters of trial 1: AP (10. 59 cm), LR (9.94 cm), DH (7.14 cm), LH (5.74 cm) was the T1 the one that obtained the highest values, while the BF (13.06 g), BS (3.61 g) the T4 was the one that obtained the highest values. In trial 2: T1 registered high values in the PA 30 days with 26.08 cm, while at 60 and 90 days T4 presented plants with greater height with 54.66 and 82.44 cm; in the parameters of productive: NF (48), LF (13.94 cm) and T1 obtained the highest averages, in the DF (11.02 cm), PFF (992.78 g) the T3 was superior, in the PSF (216. 43 g), BFT (1927.10 g), BST (411.35 g) and REN (3503.82 kg/ha.) the T4 stood out more than the rest of the treatments, which obtained a superior cost/benefit ratio with 53.04 dollars for each dollar invested, being the applications with seaweed acceptable to enhance the size, quality and yield of the bell pepper crop.